Development of the Base Physics (BASIC) Website to Improve High School Physics Science Literacy in the Merdeka Curriculum - Azmar, Azmar; Widyawati, Dian; Septiyanto, Rahmat Firman; Guntara, Yudi Firman (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
This study developed a website-based learning media, Base Physics (BASIC), to improve high school students' science literacy in physics following the Merdeka Curriculum. The Research and Development (R&D) method was used with the 4-D model (Define, Design, Develop, Disseminate). This media is designed to overcome the limitations of learning resources and provide additional references that are interactive and easily accessible. This study involved 35 students of class XII IPA at SMAN 6 Serang City and three expert validators who assessed the aspects of content, Design, and language. The validation results showed BASIC had a feasibility level of 96%, while the limited trial obtained positive responses from students with a percentage of 82%. This media is recognised for improving understanding of physics concepts, scientific thinking skills, and student engagement in learning. Thus, BASIC can be an innovative learning medium that supports physics science literacy in schools. This research recommends further development in Design and material coverage and evaluation of its effectiveness on student learning outcomes.